Association between composite dietary antioxidant index and epilepsy in American population: a cross-sectional study from NHANES - Yuhao Zhang; Junyi Shen; Hao Su; Chunyan Lin (BMC, 2024)
Abstract Background Epilepsy is a major global health challenge, affecting approximately 50 million people across the globe and resulting in significant economic impacts on individuals and society. Oxidative stress is implicated in the pathogenesis of epilepsy, highlighting the potential of antioxidant-rich dietary patterns in offering preventive and protective benefits by mitigating oxidative stress. The Composite Dietary Antioxidant Index (CDAI) provides a measure for assessing dietary antioxidant intake, yet its link to epilepsy remains unexplored. Methods Our analysis utilized data from the National Health and Nutrition Examination Survey (NHANES) spanning 2013 to 2018, including 20,180 screened participants. Weighted logistic regression models were employed to examine the association between the CDAI and epilepsy prevalence. Non-linear associations were explored through restricted cubic splines (RCS), and the relationships between individual antioxidant components within the CDAI and epilepsy were also assessed. Results After adjusting for potential confounders, a negative association between the CDAI and epilepsy was suggested (OR = 0.991; p = 0.087, 95% CI [0.819,1.014]). Stratification of CDAI into quartiles revealed a significantly reduced risk of epilepsy in higher CDAI quartiles (Q3 and Q4) compared to the lowest quartile (Q1) (Q3: OR = 0.419; p = 0.030, 95% CI [0.192, 0.914]; Q4: OR = 0.421; p = 0.004, 95% CI [0.239, 0.742]), with a significant trend observed across quartiles (p for trend = 0.013). RCS analysis suggested a nonlinear association between CDAI levels and epilepsy (non-linear p = 0.049), which, however, was not statistically significant after full adjustment (non-linear p = 0.103). Additionally, significant negative correlations with epilepsy were observed for vitamin A and zinc (Vitamin A: OR = 0.999; p = 0.012, 95% CI [0.998, 1.000]; Zinc: OR = 0.931; p = 0.042, 95% CI [0.869, 0.997]). Conclusions Our research indicates a correlation where higher CDAI levels correspond to a reduced risk of epilepsy. Therefore, embracing a diet rich in antioxidants could be beneficial in preventing epilepsy. This finding holds considerable potential for shaping future strategies in both epilepsy prevention and treatment.